Analysis of the application value of prophylactic ileostomy after for middle and low rectal cancer surgery - Yang Guohua; Yi Xiaojiang (结直肠肛门外科)
[Objectives] To explore the application value of prophylactic ileostomy (PI) after middle and low rectal cancer surgery. [Methods] Clinical data were collected from 948 rectal cancer patients admitted to the Gastrointestinal Surgery Department of Guangdong Provincial Hospital of Traditional Chinese Medicine between January 2013 and December 2023. According to the exclusion criteria, 195 patients were excluded, 753 patients were included in the final analysis. Patients were categorized into the PI group (n＝333) and the non-PI group (n＝420) based on whether they received PI after middle and low rectal cancer surgery. The operative and postoperative indicators were compared between the two groups. [Results] In terms of surgery-related indicators, there were no significant differences between the two groups in emergency surgery, laparoscopic surgery, surgical blood loss, and surgical blood transfusion (P>0.05). The proportion of patients in the non-PI group who used linear cutter closure device nail number > 1, anastomosis-to-anal margin distance< 5 cm, and operation time > 180 minutes was significantly lower than that in the PI group (P<0.001). In terms of postoperative-related indicators, there were no significant differences in anastomotic leakage, other complications, ICU admission, and second surgery between the two groups (P>0.05). The PI group had a lower proportion of patients requiring secondary hospitalization and anal canal placement, shorter hospital stays and pelvic drainage tube removal times, and higher hospitalization costs compared to the non-PI group, with statistical significance (P<0.05). [Conclusion] PI after middle and low rectal cancer surgery improves outcomes related to secondary hospitalization and anal canal placement, shortens hospital stays and pelvic drainage tube removal times, demonstrating good application value and providing a reference for clinical stoma decision-making.